In Situ Evaluation of Carbon Steel Corrosion under Salt Spray Test by Electrochemical Impedance Spectroscopy. Issue 10 (23rd June 2020) - Ito, Minoru; Ooi, Azusa; Tada, Eiji; Nishikata, Atsushi
Abstract : Electrochemical Impedance Spectroscopy was utilized to investigate the corrosion behavior of carbon steel in a salt spray test (SST) chamber. The salt spray was applied using 5% NaCl solution at 35 °C. A two-electrode cell comprising a pair of identical carbon steel electrodes embedded in epoxy resin were placed at six different angles (0°, 30°, 45°, 60°, 75°, and 90°) to the horizontal in the chamber. The corrosion rate (CR) of the carbon steel samples and the thickness of the solution film formed on the sample surface were evaluated from the impedances at low and high frequencies, respectively. The CR of carbon steel fixed horizontally (0°) exhibited a low value compared with that fixed at other angles. When the angle changed from 30 to 75°, the solution film thickness decreased greatly, but there was no significant difference in the CR. The CR of carbon steel under the employed SST conditions was more than five times higher than that in a bulk 5% NaCl solution under natural convection. The corrosion mechanism of carbon steel in the SST chamber is also discussed.